Feasibility Analysis Of Gsm-R System For Railways In Indonesia: Case Study Of Jakarta Bandung High Speed Train - Riyantika, Regina; Gunawan, Dadang (Publikasi Indonesia, 2023)
High-speed railway technology development necessitates the development of a communication system that supports various components of train operation facilities, such as train control, safety communication, and others. The construction of fhigh-speed railway in Indonesia in the Jakarta-Bandung area uses the Chinese Train Control System (CTCS) Level 3 signaling system, which makes the Global System for Mobile Communication-Railway (GSM-R) a wireless signaling network system. Because there are already existing GSM-based public telecommunications services, known as public GSM, on the same frequency used by a number of cellular operators in Indonesia, the use of GSM-R poses implementation challenges. This will result in reduced service quality and revenue for protected cellular network operators due to the use of these frequency bands to support the operation of high-speed railway services in Indonesia. In this study, an evaluation was carried out to look for other potentials from using the GSM 900 MHz frequency band, which can be used as an option to be implemented on high-speed trains in Indonesia. The research begins with calculating the estimated potential loss of revenue from using telecommunications network operators. This data will be analyzed in terms of the economic feasibility of several other frequency band choices for implementing the GSM 900 MHz frequency band on high-speed trains in Indonesia, so that it is hoped that this will become a new consideration that can become a solution and recommendation in the application and use of GSM-R technology in Indonesia.